-8u-17=-3(u+9)

Simple and best practice solution for -8u-17=-3(u+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8u-17=-3(u+9) equation:



-8u-17=-3(u+9)
We move all terms to the left:
-8u-17-(-3(u+9))=0
We calculate terms in parentheses: -(-3(u+9)), so:
-3(u+9)
We multiply parentheses
-3u-27
Back to the equation:
-(-3u-27)
We get rid of parentheses
-8u+3u+27-17=0
We add all the numbers together, and all the variables
-5u+10=0
We move all terms containing u to the left, all other terms to the right
-5u=-10
u=-10/-5
u=+2

See similar equations:

| -16.69-4.6f-15.16=-0.3f+12.87 | | 28=-6v+2(v+4) | | 6x+30-5x=35 | | 20-15v=-16v | | 19q+18=-18+17q | | 7n-8=-8+12n-7n | | 99=3(-4x+1) | | 15=0.5+3/2x+10 | | (12-7/2y)/((7/8y)-3)=0 | | 7x-2=-2x-24 | | 4f+8=8f+2 | | -480+30t^2=-400 | | 3x-4-5x=x+4 | | 16-t^2=4/3 | | 480-30t^2=400 | | -5-6n+6=19 | | (1/3)x+3=15 | | 9c+10=2c-9-9 | | -9+5p-10=10p+6 | | -7f-10=10-9f | | 210t+68=56t+1164 | | -9+3n=-10n+4 | | x+.2x=450 | | 210t-68=56t-1164 | | 5v−1=4v−9 | | 7g-8=5g | | 25x+62=4 | | 2(n-5)+2n=38 | | 0.002(1-x)+0.01(x-3)=1 | | 0.05(2)^n=0 | | 180=110+2x+5x | | x(2x+30)=4400 |

Equations solver categories